Reaffirmation of State Control Over Land: Analysis of Legal Certainty After Constitutional Court Decision No. 185/PUU-XXII/2024 - Suyanto Suyanto (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study examines the constitutional reaffirmation of state control over land following Constitutional Court Decision No. 185/PUU-XXII/2024. It analyzes legal certainty, agrarian governance, and the balance between state authority and private land rights in Indonesia. This study presents a new perspective on the IKN policy and Constitutional Court jurisprudence by examining how Constitutional Court Decision No. 185/PUU-XXII/2024 reaffirms state control over land, enhances legal certainty, and highlights the social function of land rights, in the framework that follows the decision. This study employed a normative juridical approach, incorporating statutory, case, conceptual, and historical perspectives. The Constitutional Court Decision No. 185/PUU-XXII/2024 reinforces state control over land, emphasizing the staatbeheerrecht principle in alignment with Article 33 of the 1945 Constitution while limiting excessive liberalization of land rights. The absence of implementing regulations post-decision raises concerns over legal certainty, highlighting the need for coherent regulations to reconcile constitutional demands with investment governance and land administration. Future regulations must establish timelines and evaluation mechanisms for HGBs to prevent legal gaps and ensure a balance between investment certainty and agrarian justice. This decision reverses the trend of liberalizing land rights in the IKN area, which could disregard the principle of social justice.